Impact of Combat Deployment on Psychological and Relationship Health: A Longitudinal Study. Issue 1 (24th January 2014) - Cigrang, Jeffrey A.; Wayne Talcott, G.; Tatum, JoLyn; Baker, Monty; Cassidy, Daniel; Sonnek, Scott; Snyder, Douglas K.; Balderrama‐Durbin, Christina; Heyman, Richard E.; Smith Slep, Amy M.
<x xml:space="preserve">Abstract</x> Although previous research has indicated an elevated prevalence of posttraumatic stress disorder (PTSD) and other mental health problems among veterans of Operations Iraqi Freedom and Enduring Freedom following deployment, most of this research has been cross‐sectional and has focused on a limited range of military groups and outcome criteria. This investigation was a longitudinal study of U.S. Air Force security forces assigned to a year‐long high‐threat ground mission in Iraq to determine the degree to which airmen's emotional and behavioral health and committed relationships were adversely impacted by an extended deployment to a warzone. Participants were a cohort of 164 security forces airmen tasked to a 365‐day deployment to train Iraqi police. Airmen completed study measures both prior to and 6–9 months following deployment. Rates of deterioration in individual and interpersonal adjustment were both significant and medium to large in magnitude of effect, d = 0.43 to 0.90. Results suggest that the negative effects of deployment are related to levels of traumatic experiences and do not spontaneously remit within the first 6–9 months following return from deployment—particularly among those service members having relatively lower levels of social support.